Structural and logical model of transport maritime functioning based on modeling information technology - Natalya Logunova; Sergei Chernyi; Elena Zinchenko; Denis Krivoguz; Sergey Sokolov; Anatoliy Nyrkov (Economies, 2022)
The article presents the sectoral structure of cruise (maritime) tourism and identifies the factors influencing the level of demand and supply of cruise tourism products. The sources of the influence of the cruise industry on the economic growth of the state and the welfare of its citizens are also considered. On the basis of specific features of cruise tourism functioning and the peculiarities of creating a cruise tourism product, a model of the functioning of a cruise (maritime) tourism complex has been built. Representation of the relationship of tourist needs according to the hierarchy of needs and a species classification of cruise tourism and the industries involved in its development is also given. The model of indicators and the structural components described are built in an environment of geoinformation modeling.
Keywords: 330; COVID-19; cruise industry; cruise tourism; maritime; model; modeling; transformation